Highly enantioselective ylide-mediated synthesis of terminal epoxides - CONNON, STEPHEN (My University, 2012)
The highly efficient asymmetric epoxidation of aldehydes by methylene transfer is now possible using new sulfonium salts
PUBLISHED
Keywords: Chemistry